Sustainably restoring biodiversity of degraded ecosystems in the miombo forests along the Lobito line: Low Emission Landscapes (LELS) Zambia 2025 consultation session report - Ngaiwi, Mary Eyeniyeh; Aja, Daniel; Sylvester, Janelle M.; Castro Nunez, Augusto (2025)
The Low-Emission Landscapes (LELS) team at the Alliance of Bioversity International and CIAT is dedicated to providing the best available science to guide the transition toward low-emission landscapes. Led by Dr. Augusto Castro-Nuñez, this research sub-lever develops and scales evidence-based solutions that transform food and land systems into low greenhouse gas emitters, while delivering sustainable development co-benefits.